2010
DOI: 10.17221/49/2008-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Quality of rabbit meat and phyto-additives

Abstract: Simonová M.P., Chrastinová Ľ., Mojto J., Lauková A., Szábová R., Rafay J. (2010): Quality of rabbit meat and phyto-additives. Czech J. Food Sci., 28: 161-167.The consumption of healthy and nutritive food (rich in proteins and low in cholesterol and lipid contents) is a preferred factor with the contemporary consumers. In addition, natural alternatives are requested to replace the additives used up to now but recently banned. To reach the above given condition, phyto-additives represent a good alternative. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
19
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 23 publications
(28 reference statements)
9
19
2
6
Order By: Relevance
“…Chrastinová et al (2010) demonstrated that probiotics increased protein and fat contents in rabbit's carcass meat. Also, Simonová et al (2010) found that meat of rabbits fed diets supplemented with probiotic had the highest fat content compared with the control group. …”
Section: Carcass Traitsmentioning
confidence: 95%
“…Chrastinová et al (2010) demonstrated that probiotics increased protein and fat contents in rabbit's carcass meat. Also, Simonová et al (2010) found that meat of rabbits fed diets supplemented with probiotic had the highest fat content compared with the control group. …”
Section: Carcass Traitsmentioning
confidence: 95%
“…According to Ayala [100] dietary supplementation with dried oregano improved rabbit performance, while Pogany-Simonova et al [99] reported that oregano and sage extracts improved rabbit health and carcass amino acid composition. Other researchers [97,98] found that oregano essential oil had no effect on performance parameters of rabbits and significantly increased the antioxidative capacity of raw and thermally treated carcasses during refrigerated storage.…”
Section: The Use Of Aromatic Plants In Rabbit Nutritionmentioning
confidence: 99%
“…Supplementation with alternative substances, such as probiotics, prebiotics, enzymes and organic acids, has been studied in rabbits, with interesting results emerging (Falcão-e-Cunha et al, 2007;Rotolo et al, 2014). However, the number of phyto-studies remains limited (Botsoglou et al, 2004;Krieg et al, 2009;Arafa et al, 2010;Simonová et al, 2010;Ayala et al, 2011;Szabóová et al, 2012;Rotolo et al, 2013). L. salicaria (LS) is a flowering plant, which is commonly known as purple loosestrife, belonging to the Lythraceae family.…”
mentioning
confidence: 99%